Perkembangan dan Problematika Radio Komunitas di Indonesia - ., Masduki (Jurnal ILMU KOMUNIKASI, 2005)
Abstract: This article is about the development of community radio in Indonesia, it is problems and solutions. Community radio in Indonesia developed as an alternative to both public radio and commercial radio after the fall of Soeharto in 1998. Two important features of community radio are that it provides all community members with equal access to information, enhancing their rights and obligations, access to justice, public accountability and also enables them to participate actively in radio management and production. Both features enhance people’s selfawareness and sense of belonging to a community. The expansion of the progressive, participatory, community ownership, and non-profit model of community radio, has become a third sector of communication beside the commercial or state media. The dynamic development of community radio in Indonesia faced several problems starting from it is definition, implementation of regulation until standards of programmes operation based on the concept of community approach and participation